The spectral analysis of some not self-adjoint operator pencil with a discontinuous coefficient - Orudzhev, H.D.; Efendiev, R.F. (Reports of the National Academy of Sciences of Ukraine, 2014)
The direct and inverse problems for the Schrödinger equation on the whole axis with complex periodic potentials and discontinuous right-hand side are investigated. The main properties of the fundamental solutions and the spectrum of the problem are studied. The inverse problem is formulated, and a constructive procedure for its solution is given.